2000
DOI: 10.4038/jnsfsr.v28i4.2622
|View full text |Cite
|
Sign up to set email alerts
|

Host attractants for the banana stem borer, Odioporus longicollis (Coleoptera: Curculionidae): identification, electrophysiological activity and behavioural bioassay

Abstract: Steam volatiles ol'freqj~ly cut hanana stem were analyzed lly comhined. gas c b r o m a t o~~a p l~y-electroai~l;enno~apl~ic detection (GC-EAD) ailtl comhined gas cl~i~c~matograplly-niass spect~.ometry (GC-MS) to iclentifi n-hexan.ol, n-hcxanal, n-pentanol and cis-3-hexc?nol as host attractants for the banana stem borer, Cldotl~oi~c~s loir,qicollis. .Idcnlities of t h e ahovc compounds were confirmed 1,y comparalivc studies with aulhcntics. Female weevils responded sligl~tly mo1.c (:EAG 1.41k !).()I) t1:han ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Dried extracts were transferred into pre weighed clean vials (2 mL) and the remaining solvent was removed under a stream of nitrogen. Dried extracts were stored in the refrigerator at 5 o C in glass vials until use for olfactometer bioassays and gas chromatography-mass spectrometry (GC-MS) analysis (Gunawardana & Dissanayake, 2000).…”
Section: Extraction Of Volatilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dried extracts were transferred into pre weighed clean vials (2 mL) and the remaining solvent was removed under a stream of nitrogen. Dried extracts were stored in the refrigerator at 5 o C in glass vials until use for olfactometer bioassays and gas chromatography-mass spectrometry (GC-MS) analysis (Gunawardana & Dissanayake, 2000).…”
Section: Extraction Of Volatilesmentioning
confidence: 99%
“…It has been reported that volatile compounds produced by the host plant coconut attracts the red weevil (Rynchophorus ferrugineus), and this strategy is now employed in combination with the aggregation pheromone of red weevil as an alternative, eco-friendly method to control red weevil of coconut plantations in Sri Lanka (Gunawardana & Swarnakanthi, 1995). Gunawardana and Dissanayake (2000) reported the isolation of volatiles, n-hexanal, n-hexanol, n-pentanol and cis-3-hexanol from the steam distillate of banana stems and investigated the synergistic effect of these compounds when blended with the pheromone. A trap has been developed to control the banana weevil Odoiporus longicollis.…”
Section: Introductionmentioning
confidence: 99%
“…(1999) have reported on the use of the aggregation pheromones Ferrolure and Ferrolure+. Gunawardena et al . (1998) identified host attractants for the weevil from freshly cut coconut bark and found that a 1:1 mixture of gamma nonanoic lactone 1 and 4‐hydroxy‐3‐methoxystyrene 2 were responsible.…”
Section: Pest Significancementioning
confidence: 99%
“…The destructiveness of this weevil is abetted by several traditional farming practices, including the removal of leaves during harvesting or pruning of offshoots, which causes incidental injuries to trees. Injured trees release highly volatile compounds (kairomones) that attract male weevils (Gunawardena et al 1998). Upon their arrival, males produce aggregation pheromones that attract both sexes, and the females begin laying eggs in soft or injured areas on the lower trunk of the tree.…”
Section: Introductionmentioning
confidence: 99%